2011
DOI: 10.1097/wad.0b013e318212ab7a
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Donepezil on Behavioral Symptoms in Patients With Alzheimer Disease

Abstract: The objective of this study was to evaluate the prevalence and treatment responsiveness of neuropsychiatric symptoms in patients with mild to moderately severe Alzheimer disease recruited in a naturalistic treatment setting in Spain. All the patients, who matched the prescribing recommendations for donepezil and were able to participate in the study, received donepezil (5 to 10 mg/d) for 6 months. The primary outcome measure was the incidence of adverse events. Secondary outcome measures were neuropsychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
(30 reference statements)
0
30
0
Order By: Relevance
“…Carrasco et al [23]: 455 participants recruited from 72 centers from Spain, assessed for 24 weeks, mean age 74 years, mean baseline MMSE 16 (moderate) and 11 (severe). Concomitant medications excluded were anticholinergic drugs, cholinergic agonists, neuromuscular blocking agents, and beta blockers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Carrasco et al [23]: 455 participants recruited from 72 centers from Spain, assessed for 24 weeks, mean age 74 years, mean baseline MMSE 16 (moderate) and 11 (severe). Concomitant medications excluded were anticholinergic drugs, cholinergic agonists, neuromuscular blocking agents, and beta blockers.…”
Section: Resultsmentioning
confidence: 99%
“…The first unambiguous demonstration of donepezil's beneficial impact on behavioral symptoms in patients with the moderate-severe stage was provided by Carrasco and coworkers [23]. The main effects included the improvement of neuropsychiatric and cognitive functions and the reduction of caregiver burden.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as the MTA-scale scores differentiate between moderate to severe AD patients with a sensitivity of 70–100% and a specificity of 67–96%, according to the severity of the condition of participants, subgroup analysis will be applied in the statistical analysis. Furthermore, donepezil is approved by the FDA to treat the symptoms of mild to moderate AD [24, 25] and studies have shown that it can improve the neuropsychiatric, cognitive, and global functions [3234]. Accordingly, donepezil was chosen as a positive control in this trial.…”
Section: Discussionmentioning
confidence: 99%